ZWZ-3, a Fluorescent Probe Targeting Mitochondria for Melanoma Imaging and Therapy - Liu, Zengjin; Wang, Hailan; Sun, Changzhen; He, Yuanmin; Xia, Tong; Wang, Jianv; Xiong, Xia; Zhang, Qingbi; Yang, Sijin; Liu, Li (Frontiers in Pharmacology, 2022)
The incidence of melanoma is increasing rapidly worldwide due to its increased drug resistance and high metastatic. Here, we designed and synthesized a novel hemicyanine-based fluorescent probe ZWZ-3 and investigated its apply for imaging and treating melanoma in vitro and in vivo. ZWZ-3 preferentially accumulated in the mitochondria of melanoma cells via a process that depended on the organic anion-transporting polypeptide (OATP). In addition, we investigated the effect and molecular mechanism of ZWZ-3 in melanoma. In vitro studies showed that ZWZ-3 promoted the generation of reactive oxygen species and induced mitochondrial-mediated cell apoptosis based on upregulation of Bax and the activation of caspase-3, caspase-9, and PARP. Importantly, ZWZ-3 also induced autophagy by downregulating P62, while upregulating LC-3II, Atg5. It significantly suppressed tumor growth of A375 xenograft tumor model in mice, without obvious side effects. Histological and immunohistochemical analyses revealed that ZWZ-3 also induced apoptosis and inhibited tumor cell proliferation. Thus, ZWZ-3 represents a novel theranostic agent that can be used to effectively target, detect, and treat melanoma. it may also help to monitor disease progression and response to treatment.